Inside the War on Poverty: The Impact of Food Stamps on Birth Outcomes - Almond, Douglas; Hoynes, Hilary W.; Schanzenbach, Diane Whitmore (The Review of Economics and Statistics, 2011)
This paper evaluates the health impacts of a signature initiative of the War on Poverty: the introduction of the modern Food Stamp Program (FSP). Using variation in the month FSP began operating in each U.S. county, we find that pregnancies exposed to FSP three months prior to birth yielded deliveries with increased birth weight, with the largest gains at the lowest birth weights. We also find small but statistically insignificant improvements in neonatal mortality. We conclude that the sizable increase in income from FSP improved birth outcomes for both whites and African Americans, with larger impacts for African American mothers.